Pengaruh Kepemimpinan Transformasional Terhadap Organizational Citizenship Behaviour (Studi Kasus PT Komatsu Undercarriage Indonesia) - Febyola Veneta; Sholihati Amalia (Jurnal Riset Bisnis dan Investasi, 2018)
The purpose of this research is to analyze the influence of transformational leadership on organizational citizenship behavior. This research uses quantitave descriptive method. The sample in this study was 150 employees of Komatsu Undercarriage Indonesia Ltd, using non-probability sampling - saturation sampling. The collection of information in this study was conducted by providing questionnaires to employees and analyzed by using descriptive analysis, correlation, regression, coefficient of determination, and hypothesis testing. The results of this study indicate that transformational leadership affects organizational citizenship behavior by 31,5% and the rest is influenced by other factors. Analysis results show that transformational leadership has a significant effect on organizational citizenship behavior.